An optimal target cost contract with a risk neutral owner. Issue 5 (19th August 2014) - Hosseinian, S. Mahdi; Carmichael, David G.
Abstract : Purpose: Target cost contracts are commonly used to share the monetary outcome of work or a project. However, discussion is ongoing, as to what constitutes optimal sharing. This paper examines optimal sharing and derives a result for defined risk assumptions on the owner (risk neutral) and contractor (risk averse ranging to risk neutral). Design/methodology/approach: The derivation is based on solving a constrained maximization problem using ideas from principal-agent theory. Practitioners were engaged in a designed exercise in order to validate the approach and propositions. The influence of the contractor's level of risk aversion, the cost uncertainty and the contractor's effort effectiveness are examined. Findings: The paper shows that, at the optimum, the sharing ratio between contractor and owner needs to reduce and the fixed fee needs to increase when the contractor becomes more risk-averse, the level of the cost uncertainty increases, or the effectiveness of the contractor effort decreases. Practical implications: The paper's findings provide practitioners with a useful benchmark for outcome sharing in target contracts. Originality/value: Existing work on outcome sharing in target contracts is limited to being qualitative and anecdotal in nature. This paper extends existing knowledge by providing a quantitative treatment of optimal sharing.